Optimal management of website under adverse impacts conditions. (March 2020) - Churakov, D; Tsarkova, E; Vorotnikova, T; Belyaev, A
Abstract: The paper considers a mathematical model for managing a website of a company operating in a competitive environment. Management is carried out in order to maximize profits. Optimal control actions is determined using Pontryagin's maximum principle. Numerical solution is obtained using iteration algorithm based on gradient descent method. The obtained results form the basis of a software application that can be used as a management decision support system.